The Effect of Plyometric Training Methods on The Results of Start Jump Distance in The Sport of Swimming - Darmawan Mukti Wibowo; Dede Rohmat Nurjaya; Bambang Erawan; Mulyana Mulyana (Universitas PGRI Palembang, 2025)
Plyometrics is an explosive physical training method used to increase power output, force production, and speed. Plyometrics is a way to push muscles to achieve maximal strength quickly and thus serves to increase explosive-reactive power through a variety of movements and is a popular training approach. Therefore, plyometric training is expected to have an effect on the results of the starting jump distance, and researchers aim to study more deeply the effect of plyometric training on the results of the starting jump distance in swimming. This study uses a quantitative approach with an experimental method with a One Group Pretest-Posttest Design research design. The population in this study involved 70 Tritons swimming club athletes located at the Horizon Swimming Pool, Bandung City, then the sample used was 15 people selected using purposive sampling techniques, with the instruments used being taken from the results of measuring the distance of the swimming start jump with the Kinovea application. The data were processed and analyzed using a normality test withShapiro Wilkthen analyzed using the T test with SPSS 25. The T test value is with a Sig. (2-tailed) value of 0.000, based on the test results, the Sig. (2-tailed) value <.05 so that H0 is rejected. then it can be concluded that there is a significant influence between plyometric training on the results of the start jump distance of swimming sports. Thus, because of this significance, it can be seen that plyometric training can affect the start jump distance of swimming sports.